A Low-Cost Anthropometric Walking Robot for Reproducing Gait Lab Data - Rogério Eduardo da Silva Santana; Agenor de Toledo Fleury; Luciano Luporini Menegaldo (Applied Bionics and Biomechanics)
Human gait analysis is one of the resources that may be used in the study and treatment of pathologies of the locomotive system. This paper deals with the modelling and control aspects of the design, construction and testing of a biped walking robot conceived to, in limited extents, reproduce the human gait. Robot dimensions have been chosen in order to guarantee anthropomorphic proportions and then to help health professionals in gait studies. The robot has been assembled with low-cost components and can reproduce, in an assisted way, real-gait patterns generated from data previously acquired in gait laboratories. Part of the simulated and experimental results are addressed to demonstrate the ability of the biped robot in reproducing normal and pathological human gait.